TREATMENT OF BENIGN ESOPHAGEAL STRICTURE - V. L. Belevich; D. V. Ovchinnnikov (Вестник хирургии имени И.И. Грекова)
The article presents an analysis of long-term experience of treatment of 128 patients with benign esophagus and esophageal anastomosis strictures in Kirov Military Medical Academy. This significant data included all possible variations of scarry esophageal strictures according their etiology, localization and the extension. The wide range of methods, which involved the different variants of bouginage, balloon dilation, stenting, electrosurgical dissection and resection of the stomach, were applied in treatment of the patients. The analysis of immediate and long-term results allowed detecting the criteria of choice and indication for use of the methods or their combination. Practical recommendations reflect the strategy of each variant of treatment and have the specific character. Possible complications and negative results of irrational application of different methods were presented. The immediate and long-term results gave evidence of the successful treatment of the patients with scarry esophagus and esophageal anastomosis strictures.